Spatial Locative Relativization in Three African Varieties of Portuguese: Unity in Diversity and Diversity in Unity - Tjerk Hagemeijer; Rita Gonçalves; Nélia Alexandre (Languages, 2024)
This paper investigates the formation of spatial locative relativization in three African varieties of Portuguese. While research on relative constructions in Portuguese has deserved considerable attention in the literature, it tends to focus on the European and Brazilian varieties, with locative relativization being only marginally addressed. Using data extracted from spoken corpora of contemporary, urban varieties of Angolan, Mozambican, and Santomean Portuguese, we aim to discuss whether there is a correlation between syntactic and semantic variables and the selection of the two main locative relative morphemes, onde ‘where’ and que ‘that’. Overall, the three varieties at stake behave similarly with respect to the analyzed syntactic variables and follow the tendency found in Portuguese varieties toward the use of pied-piping and P-chopping as the dominant relativization mechanisms, independent of the syntactic relation between the antecedent and the relative clause. Semantically, we identified some fine-grained differences between the three varieties, with Santomean Portuguese generally being the outlier or one of the outliers. Crucially, definiteness of the head noun stands out as the one variable that plays a major role in the selection of the relative morpheme: [−definite] head nouns show a proportionally higher preference for que in both AP and STP, which is particularly visible with bare nouns in the latter. This motivates the hypothesis that less specified head nouns show a preference for the un(der)specified relative morpheme que. We further show that the role of language contact is at best very limited.